Osteoporosis is a novel risk factor of infections and sepsis: A cohort study. (July 2022) - Zhang, Xiaowen; Man, Kwong-Wai; Li, Gloria Hoi-Yee; Tan, Kathryn CB; Kung, Annie Wai-Chee; Cheung, Ching-Lung
Summary: Background: Accumulating evidence suggests the interaction of bone metabolism and the immune system, but how bone health is associated with the risk of infections remains unknown. Methods: This study aimed to investigate the relationship of bone mineral density (BMD) with the risk of common infections and sepsis in Hong Kong Osteoporosis Study (HKOS). A prospective cohort study, initiated in 1995 and followed until 31 December 2020, of 5, 717 participants examined the association of BMD at three skeletal sites (lumbar spine, femoral neck, and total hip) with common infections - pneumonia, urinary tract infection (UTI), skin infection, and sepsis. Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI). Findings: During the median follow-up of 17 years, higher BMD T-scores at the femoral neck and total hip were significantly associated with the reduced risk of pneumonia (HRs 0.89 and 0.87; 95% CIs 0.82 to 0.98 and 0.81 to 0.95), UTI (HRs 0.85 and 0.86; 95% CIs 0.76 to 0.94 and 0.78 to 0.95), skin infection (HRs 0.85 and 0.82; 95% CIs 0.74 to 0.97 and 0.73 to 0.93), and sepsis (HRs 0.83 and 0.82; 95% CIs 0.71 to 0.97 and 0.72 to 0.94). A significant association was observed for the lumbar spine BMD T-score with the risk of skin infection (HR 0.86; 95% CI: 0.78 to 0.95) but not with other infections and sepsis. Similarly, participants with osteoporosis, but not osteopenia, were significantly associated with an increased risk of infections and sepsis compared to those with normal BMD. Interpretation: BMD is a novel risk factor of infections and sepsis. People with low BMD, particularly those with osteoporosis, are at higher risk of infections and sepsis than those with normal BMD. Further studies on whether improving bone health can reduce the risk of infections and sepsis are warranted. Funding: None.